Factors involved in the recruitment and retention of voluntary blood donors in South Kivu (Democratic Republic of Congo), results from a qualitative study - Susanne Mbaka Ngunza; Isabelle Aujoulat (Discover Public Health)
Abstract Background and objective Voluntary blood donations remain a major concern in the Democratic Republic of Congo, increasing morbidity and mortality due to shortages of safe blood. Local studies show low rates of recruitment and retention of voluntary donations, as well as a high attrition rate of former donors. The psychosocial factors involved in deciding to become and remain a voluntary blood donor in sub-Saharan Africa remain poorly understood. Our study therefore aimed to explore the motivational factors and perceptions involved in voluntary blood donation in South Kivu. Materials and methods We conducted 20 individual interviews, and three focus group discussions were conducted with a total of 26 volunteer donors. As a way of triangulation, two additional focus-groups were held with 19 non-donors. The individual interviews were analysed thematically, using a starting list of 3 predefined units of analysis, namely: initiation, maintenance, and cessation of voluntary blood donation. The data was analysed inductively within these predefined units of analysis to generate possible factors of motivation that were then presented and further discussed during the focus-groups discussions with donors and non-donors. Results Fear presented as a factor influencing the decisions to donate blood either positively or negatively, from recruitment to maintenance to cessation of donation. Other motivational factors were found to be linked to the perceived meaning of voluntary donation, such as the meaning given to the blood voluntary donation and material or non-material expectations. Our results suggest that expectations for material rewards are still high in the context of poverty. Conclusion In conclusion, many motivational factors may act as incentives or barriers to voluntary blood donation, including high expectations towards the transfusion system. Local particularities need to be considered when promoting voluntary blood donation. The fear of being abused by the system needs to be addressed, by enhancing accessibility to transfusions.